Pengaruh Leverage dan Profitabilitas terhadap Tax Avoidance dengan Moderasi Koneksi Politik Rentan Waktu Covid-19 - Dinda Andrianti; Nur Ainiyah; M. Bahril Ilmiddaviq (Indonesia Economic Journal, 2025)
This study aims to examine the effect of leverage and profitability on tax avoidance with political connections as a moderating variable in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Tax avoidance is a legal strategy used by companies to minimize tax burdens, potentially affecting state revenues. Leverage is measured using the Debt to Asset Ratio (DAR), profitability with Return on Assets (ROA), tax avoidance with the Effective Tax Rate (ETR), and political connections are identified based on ownership, commissioners, or directors with political ties. This research adopts a quantitative approach using the Moderated Regression Analysis (MRA) method. The sample consists of 15 companies selected through purposive sampling, resulting in 60 observations. The results show that leverage has a significant positive effect on tax avoidance, while profitability does not have a significant effect. Political connections strengthen the relationship between leverage and tax avoidance but do not moderate the relationship between profitability and tax avoidance. This study contributes to the accounting and taxation literature and provides practical implications for policymakers in formulating fair and accountable tax regulations, especially in strategic sectors such as mining.